2011
DOI: 10.1523/jneurosci.1379-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Burst Transcranial Magnetic Stimulation Alters Cortical Inhibition

Abstract: Human cortical excitability can be modified by repetitive transcranial magnetic stimulation (rTMS), but the cellular mechanisms are largely unknown. Here, we show that the pattern of delivery of theta-burst stimulation (TBS) (continuous versus intermittent) differently modifies electric activity and protein expression in the rat neocortex. Intermittent TBS (iTBS), but not continuous TBS (cTBS), enhanced spontaneous neuronal firing and EEG gamma band power. Sensory evoked cortical inhibition increased only afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
190
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 73 publications
(96 reference statements)
7
190
3
2
Order By: Relevance
“…This suggests that TMS delivers a strong volley that predominantly affects inhibitory neurons (55,56), most likely of the parvalbumin-expressing type (57). Because of their soma targeting on pyramidal neurons (58), and possibly because of their far-reaching axonal-dendritic structure (59) enhancing TMS sensitivity (60), these interneurons may impose strong synchronized inhibition in the affected cortical network (10).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TMS delivers a strong volley that predominantly affects inhibitory neurons (55,56), most likely of the parvalbumin-expressing type (57). Because of their soma targeting on pyramidal neurons (58), and possibly because of their far-reaching axonal-dendritic structure (59) enhancing TMS sensitivity (60), these interneurons may impose strong synchronized inhibition in the affected cortical network (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, a stronger reduction in PV expression obtained with five blocks of iTBS (at 15-minute intervals; Volz and others 2013) can also last for days while the decrease in CB caused by five cTBS blocks recovers more rapidly (Benali and others 2011). Early after iTBS (10-20 minutes) the immediate early gene product c-Fos and presynaptic GAD65 show enhanced expression, indicating that iTBS increases neuronal activity including that of GABAergic neurons (Fig.…”
Section: Modulation Of Cortical Gabaergic Inhibition By Noninvasive Bmentioning
confidence: 82%
“…*P < .05, **P < .01, ***P < .001. Part B of the figure has been redrawn using data of Benali and others (2011) and Hoppenrath and Funke (2013).…”
Section: Modulation Of Cortical Gabaergic Inhibition By Noninvasive Bmentioning
confidence: 99%
“…It has been shown that the expression of products of the early genes (c-Fos, zif268), the GA-BA-synthesizing enzymes (GAD65 and GAD67) and also the expression of NMDA-1 receptors in the hippocampus changed under the influence of rTMS in the neocortex of rats, which indicated the initiation of the process of synaptic plasticity [28]. The presence of immediate and long-term reactions to rTMS is confirmed by the results of the current study.…”
Section: Discussionmentioning
confidence: 99%